Handling COVID-19: Best Practices for Agribusiness - Michelle Danyluk; Tom Maddox; Laurel Dunn (EDIS)
COVID-19 is spread primarily via close person-to-person contact, or when virus-containing droplets expelled during coughing or talking contaminate a surface that is later touched by a healthy individual. While most feed and supply stores continue to operate during disease outbreaks and other emergencies, preventive steps can be taken to protect the health of employees and customers.